Error Analysis Of The Essays Written By English Department Students Of Halu Oleo University - Akbar, Aidil; Sidu Marafat, La Ode; Lio, Asrun (Journal of Language Education and Educational Technology (JLEET), 2019)
Errors have long been the obsession of language instructors and researchers. Before, errors were looked at as a problem that should be eradicated. However, errors are now considered as a device that learners use and from which they can learn, they provide evidence of the learner's level in the target language , they contain valuable information on the learning strategies of learners , and they also supply means by which teachers can assess learning and teaching and determine priorities for future effort. Thus, conducting error analysis is therefore one of the best ways to describe and explain errors committed by the EFL learners. The objective of this study is to identify type of errors on the EFL that is commonly found in students writing performances according to Surface Strategy taxonomy, to identify the possible causes of students’ errors in their writing performances and to identify kind of grammatical errors in students writing performances. This study employed a qualitative method. Sources of data were students’ writing performance in essay form. The result shows all of the four types of errors according to surface strategy taxonomy such as omission, misinformation, addition, and malformation/disordering, the result shows omission and misinformation are the types of errors that commonly found English department students’ essays. However, omission is the type of errors that is founded the most in students writing. The Possible causes of students’ error are: The learner doesn’t know the structural pattern. Hence, they make random response; The correct model has been insufficiently practiced; Distortion may induce by the first language. Kind of grammatical errors that is found in students’ essays are noun and verb inflection, subject-verb agreement, articles, pronouns, spellings, singular/plural form, capitalization, sentence fragments and prepositions. On the basis of these results, some pedagogical implications which might assist ESL/EFL teachers with some helpful suggestions and teaching strategies that will reduce future problems regarding writing for EFL learners.